METHODOLOGY FOR THE PROFESSIONAL PEDAGOGICAL DEVELOPMENT OF FUTURE TEACHERS BASED ON THE DEVELOPMENT OF REFLECTIVE ABILITIES - Gаvkhаrоy Оrinbоy Qizi, Yuldаshevа (PT. Antis International Publisher, 2025)
Objective: This article explores the professional pedagogical development of future teachers, emphasizing the enhancement of reflective abilities to foster analytical pedagogical thinking. The aim is to identify effective strategies for modifying pedagogical practices to achieve positive outcomes in teaching. Method: The study employs a qualitative approach, examining the processes through which future teachers develop their reflective abilities. It highlights pedagogical thinking as a key resource for guiding teachers in analyzing and adapting their professional practices. Results: The findings demonstrate that reflective abilities enable future teachers to critically evaluate their pedagogical practices, recognize their roles in teaching, and identify optimal strategies for achieving their educational objectives. Teachers who cultivate reflective thinking are better equipped to modify their approaches to meet diverse student needs and improve learning outcomes. Novelty: This article contributes to the field by presenting reflective abilities as a crucial component in the professional development of future teachers. It provides new insights into how reflective pedagogical thinking enhances the ability to assess and refine teaching practices, offering a framework for integrating reflection into teacher training programs.